On-Tissue Chemical Derivatization for Mass Spectrometry Imaging of Fatty Acids with Enhanced Detection Sensitivity - Malik Ebbini; Zicong Wang; Hua Zhang; Kelly H. Lu; Penghsuan Huang; Cameron J. Kaminsky; Luigi Puglielli; Lingjun Li (Biomolecules)
The dysregulation of fatty acid (FA) metabolism is linked to various brain diseases, including Alzheimer’s disease (AD). Mass spectrometry imaging (MSI) allows for the visualization of FA distribution in brain tissues but is often limited by low detection sensitivity and high background interference. In this work, we introduce a novel on-tissue chemical derivatization method for FAs using Girard’s Reagent T (GT) as a derivatization reagent combined with 2-chloro-1-methylpyridinium iodide (CMPI) as a coupling reagent and triethylamine (TEA) to provide a basic environment for the reaction. This method significantly enhances the detection sensitivity of FAs, achieving a 1000-fold improvement over traditional negative ion mode analysis. Our method enabled us to observe a notable depletion of oleic acid in the corpus callosum of AD mouse model brain tissue sections compared to wild-type control brain tissue sections. The reliability of our method was validated using LC-MS/MS, which confirmed the presence of eight distinct GT-labeled FAs across various tissue locations. This approach not only improves FA detection in brain tissues but also has the potential to provide a deeper understanding of FA dynamics associated with AD pathogenesis.